Gains from Crime Do metal thieves respond to raising prices of non-ferrous metals? - Brabenec, Tomáš (2011)
This paper estimates the elasticity of supply-of-offences with respect to the gains from crime. Previous studies have uncovered little evidence because standardly used proxies for gains from crime such as average income suffer substantial problems. They are slightly variable and/or may represent the opportunity cost of crime at the same time. This paper uses higly fluctuating world prices on non-ferrous metals as proxy for the gains from crime. Using monthly data about metal thefts in the Czech Republic for years 2003-2009 estimates elasticity of supply-of-offences. The estimated elasticity with respect to copper price are around 0,6.